Analisis Semiologi Pesan Moral dan Persahabatan dalam Film “Shawshank Redemptation” - Muhammad Rauf Abdul Fattah; Mochamad Rochim (UNISBA Press, 2023)
Abstract. Film plays an important role in communicating messages to its audience, one of which is a moral message. The Shawshank Redemption is a film based on a story by Stephen King and directed by Frank Darabont. Shawshank's redemption contains a lot of morals. This film contains many positive moral messages and provides many lessons. This study aims to determine the stereotyped messages contained in The Shawshank Redemption. The research methodology used in this study is qualitative research using Roland Barthes' semiotic analytic research method, with primary data sources (The Shawshank Redemption film) and secondary data (handbooks). Data collection by means of observation or close observation of the research topic, as well as reading literature (books, articles, journals, internet, dissertations, etc.). And using the triangulation method to check the research data. The results of this study were obtained by analyzing moral messages using Roland Barthes' semiotic analysis. The moral message contained in The Shawshank Redemption is taken from several scenes previously selected by the researcher, namely: courage to speak the truth and truth, act honestly, consistency in one's actions, politeness to others, patience in facing trials, discipline in everything, having a sincere heart when doing something, being serious about something, and taking responsibility in accepting actions and punishments. Abstrak. Film memegang peranan penting dalam mengkomunikasikan pesan kepada penontonnya, salah satunya adalah pesan moral. The Shawshank Redemption adalah film berdasarkan cerita oleh Stephen King dan disutradarai oleh Frank Darabont. Penebusan Shawshank mengandung banyak pesan moral. Film ini banyak mengandung pesan moral yang positif dan memberikan banyak pelajaran. Penelitian ini bertujuan untuk mengetahui pesan stereotip yang terkandung dalam The Shawshank Redemption. Metodologi penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan menggunakan metode penelitian analitik semiotika Roland Barthes, dengan sumber data primer (film The Shawshank Redemption) dan data sekunder (handbook). Pengumpulan data dengan cara observasi atau pengamatan dekat terhadap topik penelitian, serta membaca literatur (buku, artikel, jurnal, internet, disertasi, dll). Dan menggunakan triangulasi metode untuk mengecek data penelitian ini. Hasil penelitian ini diperoleh dengan menganalisis pesan moral menggunakan analisis semiotika Roland Barthes. Pesan moral yang terkandung dalam The Shawshank Redemption diambil dari beberapa adegan yang dipilih sebelumnya oleh peneliti, yaitu: keberanian untuk berbicara kebenaran dan kebenaran, bertindak jujur, konsistensi dalam tindakan seseorang, kesopanan kepada orang lain, kesabaran dalam menghadapi cobaan, disiplin dalam segala hal, memiliki hati yang tulus ketika melakukan sesuatu, serius tentang sesuatu, dan mengambil tanggung jawab dalam menerima tindakan dan hukuman.